The impact of acceptance and commitment therapy (ACT) on the psychological defense mechanism and weight loss program: A randomized controlled trial among university students during COVID-19 movement control order - Patricia Pawa, Pitil; Siti Raudzah, Ghazali (Elsevier B.V., 2023)
This study examined the effectiveness of acceptance and commitment therapy (ACT) in changing the psychological defense mechanism and promoting weight loss among overweight or obese (OW/OB) university students. A sample of 152 OW/OB university students who reported high immature and neurotic defense styles was randomly assigned into ACT, ACT-EX (ACT and structured exercise program), or a control group (CG) for a six-week intervention program. Group × time interactions showed that the BMI and all defense styles improved in the ACT and ACT-EX groups. The BMI was significantly lower in ACT-EX than in ACT, while the within-group effect size was larger in ACT than in ACT-EX for immature and neurotic defense styles. The mature defense style showed a significant improvement albeit with a small effect size in both ACT and ACT-EX. Both ACT interventions were found to be effective in promoting weight loss and improving the psychological defense mechanism, including experiential avoidance.